Effect of Helicobacter pylori-related chronic gastritis on gastrointestinal microorganisms and brain neurotransmitters in mice - Liu, Hai-Hua; Lin, Tang-Tang; Zhang, Qi-Jia; Zhang, Ling; Fang, Jin-Ying; Hu, Ling (Frontiers in Pharmacology, 2024)
The effects of Helicobacter pylori (Hp)-related chronic gastritis on gastrointestinal microorganisms or brain neurotransmitters are not fully understood. Here, this study selected SPF C57BL/6 mice to set up a Hp-related chronic gastritis experiment group and a blank control group, and used omics to explore the specific effects of Hp-related chronic gastritis on gastrointestinal microorganisms and brain neurotransmitters in mice. The Tyramine (TyrA) content in the female experiment group's brain was considerably reduced compared to the female control group (P < 0.01), and TyrA was strongly correlated with 13 gastrointestinal microorganisms with significant differences, such as Acinetobacter_baumannii (P < 0.05). The His content in the male experiment group's brain was significantly higher than that in the male control group (P < 0.05), and His was strongly correlated with four gastrointestinal microorganisms with significant differences, such as Acinetobacter_baumannii (P < 0.05). The Levodopa (DOPA) content in the female control group's brain was significantly lower than that in the male control group (P < 0.05), and DOPA was strongly correlated with 19 gastrointestinal microorganisms with significant differences, such as Achromobacter_xylosoxidans (P < 0.05). The contents of L-Glutamine (Gln), L-Glutamine (GABA), Noradrenaline hydrochloride (NE), and Adrenaline hydrochloride (E) in the female experiment group's brain were significantly lower than those in the male experiment group (P < 0.05), and Gln, GABA, NE, and E were strongly correlated with 41, 28, 40, and 33 gastrointestinal microorganisms with significant differences (P < 0.05), respectively. These results indicate that Hp-related chronic gastritis could affect gastrointestinal microorganisms and brain neurotransmitters in mice with certain gender differences, and the changes in brain neurotransmitters might be related to the changes in gastrointestinal microorganisms.